THE INFLUENCE OF TELEVISION ADVERTISING ON PURCHASE DECISION OF TEENAGERS - Bakara, Frisca Oktoviani (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2013)
Television advertising has become a new force capable of influencing the audience to do what the advertisers want, and teenagers are very promising target for producers. This study investigated the influence of television advertising on teenagers purchase decision in Manado. This research aims to analyze (1) what is the impact of television advertising (Brand Preference, Peer Group, and Pester Power) on teenagers purchase decision; (2) which impact of television advertising (Brand Preference, Peer Group, and Pester Power) has the most significant influence on teenagers purchase decision; (3) is there any significant difference between male and female on teenagers purchase decision. Theories supporting the research are advertising and purchase decision. 100 respondents of the questionnaires were distributed to teenagers who live in Manado. The data obtained were analyzed using Multiple Linear Regression and Independent Sample t-test Analysis. The findings reveales that Brand Preference, Peer Group, and Pester Power have significant influence on teenagers purchase decision. Pester Power is the greatest factor that influence teenagers purchase decision and the least significant factor is Peer Group. There is significant difference between male and female for each factors. The result shows that the television advertising has a significant influence on purchase decision of teenagers. Keywords: television advertising, purchase decision, brand preference, peer group, pester power.